The behaviour of polyurethane foam beams reinforced with thin walled steel sections for use in bus structures - Gaafar, Labib A. (Cranfield University, 1980)
The thesis is directed to the theoretical determination of the behaviour of rigid skin polyurethane foam beams reinforced with thin walled steel sections. The aim is to enable the designer to predict the behaviour of bus body structure during accident situations in order to build safe buses. A literature search has revealed that very little work has been done in this particular field of research. Thus a preliminary test programme was made to investigate the beam behaviour in bending particularly at high deflection. The test results shown in Chapter 1 gave promising results for continuing the research. Chapter 2 is directed to elastic analysis of composite beams. One of the advanced methods to predict the elastic stiffness of sandwich beams is the interfacial shear method. This assumes an interfacial shear between the core and the faces of sandwich beams. So, by considering a similar assumption, i.e. an interfacial shear between the matrix and the reinforcement, an analysis was made to predict the stiffness of composite beams. Although this method highly overestimated the stiffness, it represents a good basis for the inelastic bending analysis which is more important for the present study. Chapter • 3 shows the inelastic bending analysis of composite beams. This analysis is based on TIMOSHENKO and JAMES curvature area method. The experimental verification of the theory is shown in Chapter 4. The theory shows good agreement with the experimental results. The shape of the reinforcement was optimised for uniaxial bending. This optimum composite section showed a weight saving when it was compared with equivalent energy absorbing rectangular steel tube. Impact tests were made using a pendulum designed specially to test cantilever beams at different speed and impact energies. The test results are presented in Chapter 5. These results showed that the composite beams behaviour is similar for both static and dynamic loading. To compare the composite beam with the constituent beams, the large deflection behaviour of thin walled channel section beams made of thin sheet steel has been investigated. The experiments consisted of cantilever bending tests with the beam loaded through the shear centre and through the centroid. When loaded through the shear centre the beam buckling took place in the compression flange at the root of the cantilever. When loaded through the centroid however, it was noted that the compression flange buckled at a fixed distance from the fixed end. The general theory of thin walled beams developed by Vlasov was applied to the problem and indicated that the maximum compression stress at the free edge of the flange would be a maximum at some distance from the fixed end. The value of the maximum compression stress obtained by the general linear theory was small and its position did not coincide with the experimental position. The Vlasov analysis has been modified to include the increase in the twisting moment due to the lateral deformation- of the beam along its length. Good agreement between the modified theory and experiment both for the position of the maximum compressive stress and for the twist of the cantilever at three points along its length. Because of the very low torsional stiffness of thin walled channel sections, the small deflection theory is only applicable for small bending loads applied through the centroid and the modified theory should be used for practical loading cases.